Assessing the Validity of the Halal Consumption Congruence (HaCC) Model towards Consumer’s Purchase Intention of Malaysia’s Halal Food Products - Mahiah Said; Faridah Hassan; Muhammad Asyraf Hasim; Mohd Faizun Mohamad Yazid (Universiti Sains Islam Malaysia, 2025)
Indexed by Scopus